The Long-Term Effects of Developmental Hypoxia on Cardiac Mitochondrial Function in Snapping Turtles - Galli, Gina L. J.; Ruhr, Ilan M.; Crossley, Janna; Crossley, Dane A. (Frontiers in Physiology, 2021)
It is well established that adult vertebrates acclimatising to hypoxic environments undergo mitochondrial remodelling to enhance oxygen delivery, maintain ATP, and limit oxidative stress. However, many vertebrates also encounter oxygen deprivation during embryonic development. The effects of developmental hypoxia on mitochondrial function are likely to be more profound because environmental stress during early life can permanently alter cellular physiology and morphology. To this end, we investigated the long-term effects of developmental hypoxia on mitochondrial function in a species that regularly encounters hypoxia during development – the common snapping turtle (Chelydra serpentina). Turtle eggs were incubated in 21% or 10% oxygen from 20% of embryonic development until hatching, and both cohorts were subsequently reared in 21% oxygen for 8 months. Ventricular mitochondria were isolated and mitochondrial respiration and reactive oxygen species (ROS) production were measured with a microrespirometer. Compared to normoxic controls, juvenile turtles from hypoxic incubations had lower Leak respiration, higher P:O ratios, and reduced rates of ROS production. Interestingly, these same attributes occur in adult vertebrates that acclimatise to hypoxia. We speculate that these adjustments might improve mitochondrial hypoxia tolerance, which would be beneficial for turtles during breath-hold diving and overwintering in anoxic environments.